Pengaruh Kesadaran Wajib Pajak, Sanksi, dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi dalam Membayar Pajak Penghasilan (Studi Kasus di KPP Pratama Kota Probolinggo) - Adhela Hadi Pratiwi; M. Cholid Mawardi; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Tax is a mandatory contribution to the state to increase state revenue and support national development for the welfare of society. This study aims to determine the effect of taxpayer awareness, sanctions, and tax authorities on individual taxpayer compliance in paying income tax in Probolinggo City. This type of research used is quantitative research using primary data. The sampling technique used purposive sampling, as many as 96 individual taxpayers were calculated based on the sample size calculator application, namely Raosoft.com. This study shows that there are variables of taxpayer awareness, sanctions, and tax authorities that have a positive effect on the individual taxpayer compliance variable in paying income tax.Keywords: Taxpayer awareness, sanctions, fiskus services, individual taxpayer